2018
DOI: 10.5897/jphe2018.1073
|View full text |Cite
|
Sign up to set email alerts
|

Risky sexual behaviors and associated factors among preparatory school students in Arba Minch town, Southern Ethiopia

Abstract: There is growing evidence suggesting that young people in school are practicing risky sexual behaviors. Ethiopian people aged 10 to 24 years have emerged as the segments of the population most vulnerable to a broad spectrum of serious sexual health problems. Therefore, the main aim of this study was to assess risky sexual behaviors and associated factors among preparatory school students in Arba Minch, Southern Ethiopia. An institution based cross sectional study was conducted among 465 study participants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In this study, it was found that respondents whose use of mass media was harmful were three times more likely to engage in risky sexual behavior than respondents whose use of mass media was positive. This result is in line with Abera et al's (2018) research, which explains that someone who watches pornographic films is 8.8 times more likely to engage in risky sexual behavior.…”
Section: The Relationship Between Peer Influence and Risk Sexual Behaviorsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, it was found that respondents whose use of mass media was harmful were three times more likely to engage in risky sexual behavior than respondents whose use of mass media was positive. This result is in line with Abera et al's (2018) research, which explains that someone who watches pornographic films is 8.8 times more likely to engage in risky sexual behavior.…”
Section: The Relationship Between Peer Influence and Risk Sexual Behaviorsupporting
confidence: 90%
“…The freedom of youth in accessing the mass media and the unavoidable disclosure of information makes it difficult for mass media to be selected, including content that contains pornography (Santrock, 2016). A person who watches pornographic films is 8.8 times more likely to engage in risky sexual behavior (Abera et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the existing reproductive health (RH) services for youth are not well organized to meet youths need and much has not been done to make the health services youth friendly [6]. Adolescence/youth birth is the risk factor for maternal mortality and contraceptive prevalence is only 20% in Ethiopia [7]. Consequently, there are evidences on the low and improper utilization of the RH service and are different associated factors for it.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand research works on the issue have been done on adolescence in other regions of the country [7,14,15]. On the other hand researches done in regions were also focused on females [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Young people’s sexual behavior is also influenced by predictors such as having multiple partners, using alcohol and illegal drugs, having sex without using condoms, peer pressure, watching porn, being single, cultural, religious, not disclosing one’s HIV status, engaging in risky sexual behavior, having sex with older partners, and family disputes. 4,9,11,2127…”
Section: Introductionmentioning
confidence: 99%